PENGARUH SELF-CONGRUITY DAN CELEBRITY ATTACHMENT PENONTON VTUBER TERHADAP CONSUMER ENGAGEMENT DI YOUTUBE - Aflah Hanif Hariadi; Agung Eko Budiwaspada (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2023)
Social media engagement is important in building brand equity as a determinant of brand reputation that can be driven through self-congruity and celebrity attachment. However, there has been no research examining the relationship between self-congruity and celebrity attachment and their influence on consumer engagement in the context of VTuber personal brands as a new phenomenon that is popular internationally. This study uses a mixed-methods approach by conducting qualitative research with qualitative text analysis techniques to determine the expressions of self-congruity and celebrity attachment that emerge through viewer comments on YouTube and questionnaires. Quantitative research is conducted using PLS-SEM analysis of questionnaire responses to determine the influence of self-congruity and celebrity attachment on consumer engagement among VTuber viewers in Indonesia on YouTube content. Qualitative research found various forms of self-congruity dominated by cultural similarities between VTubers and viewers rather than personal character similarities between them. Quantitative research confirms this by finding that only social self-congruity has a positive influence on consumer engagement. Additionally, qualitative research found various forms of celebrity attachment from VTuber viewers that confirm celebrity attachment as part of brand equity. Quantitative research also found that celebrity attachment has a positive influence on consumer engagement.